2019
DOI: 10.1111/iju.13971
|View full text |Cite
|
Sign up to set email alerts
|

Hunner lesion versus non‐Hunner lesion interstitial cystitis/bladder pain syndrome

Abstract: Background Global consensus on the standardization of terminology for interstitial cystitis/bladder pain syndrome is lacking and is in the formative stages. The Workshop on Hunner lesion versus non‐Hunner lesion at the 2018 International Consultation on Interstitial Cystitis Japan discussed prevalence, performance and outcome of endoscopy, the role of histopathology, and markers. Methods A panel of experts reviewed the literature regarding Hunner lesion vs. non‐Hunner lesion interstitial cystitis/bladder pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 74 publications
(218 reference statements)
2
84
0
3
Order By: Relevance
“…1). Past studies have shown that this entity presents with distinct clinicopathological and genomic characteristics compared with other forms of IC/BPS 5–11 . This evidence suggests that IC/BPS with Hunner lesions comprises a potentially distinct disease entity with different etiology in the IC/BPS umbrella.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…1). Past studies have shown that this entity presents with distinct clinicopathological and genomic characteristics compared with other forms of IC/BPS 5–11 . This evidence suggests that IC/BPS with Hunner lesions comprises a potentially distinct disease entity with different etiology in the IC/BPS umbrella.…”
Section: Introductionmentioning
confidence: 90%
“…The workshop on IC/BPS phenotyping at the 4th International Consultation on Interstitial Cystitis Japan meeting discussed potential categorization of IC/BPS in terms of their clinical characteristics, epidemiology and bladder histology 4,8 . It was unanimously agreed that IC/BPS with Hunner lesions is a proven, clinically relevant subtype that should be regarded as a distinct disease entity.…”
Section: Categorization Of Ic/bpsmentioning
confidence: 99%
“…More pain with penetration and pain distinctly provoked during palpation of the bladder at the site of the lesion have been described. The diagnosis is made on cystoscopy, and the endoscopic features have been well described before, as are the findings of histopathological investigation (15).…”
Section: Diagnosis Of Ic/bpsmentioning
confidence: 99%
“…Some say the presence of a Hunner's lesion proves the diagnosis of BPS; but the lesions are not present in all patients with BPS. 14 The definition of an ulcer is 'an abnormal discontinuation in an epithelial surface' for example skin, mouth, stomach or bladder. Magnus Fall, Professor of Urology in Gothenburg, Sweden, suggested Hunner's ulcers (now lesions) are not always true ulcers and should therefore be called Hunner's lesions, and Fall also suggested that BPS can be subdivided into either an ulcer or non-ulcer type.…”
Section: What Is a Hunner's Lesion?mentioning
confidence: 99%
“…Magnus Fall, Professor of Urology in Gothenburg, Sweden, suggested Hunner's ulcers (now lesions) are not always true ulcers and should therefore be called Hunner's lesions, and Fall also suggested that BPS can be subdivided into either an ulcer or non-ulcer type. [14][15][16] Hunner's initial symposium was entitled 'A Rare Type of Bladder Ulcer in Women', and the pathology is still often said to be a rare finding. In 1958, Kinder and Smith reviewed all cases seen at St Peter's and St Paul's Hospitals in London over a 10-year period.…”
Section: What Is a Hunner's Lesion?mentioning
confidence: 99%